Haemostatic Variables and Menopausal Status: Influence of Hormone Replacement Therapy - Scarabin, Pierre-Yves; Plu-Bureau, Geneviève; Bara, Lucienne; Bonithon-Kopp, Claire; Guize, Louis; Samama, Meyer M (Thrombosis and Haemostasis, 1993)
Large cohort studies have shown that postmenopausal estrogen use was associated with a reduction in the risk of coronary heart disease, This putative beneficial effect of hormone replacement therapy (HRT) may be partly mediated through changes in clotting factors and fibrinolytic system. We have measured haemostatic variables in 293 consecutive healthy women aged 45-54 years who attended a health check-up centre in Paris (IPC). Premenopausal women taking hormonal therapy were excluded (n = 34). Most women using HRT were given 17-β estradiol in combination with progestin. Mean levels (m ± sd) of plasma fibrinogen, factor VII coagulant activity and plasminogen activator inhibitor (PAI) were significantly higher in postmenopausal women not taking HRT (n = 99) than in premenopausal women (n = 139) within the same decade (319 ± 52 mg/dl vs 304 ± 60 mg/dl, 107 ± 17% vs 96 ± 16%, 9.73 ± 5.71 U/ml vs 7.61 ± 4.36 U/ml respectively). Allowance for main cardiovascular risk factors made no substantial differences to the results, although the effect of the menopause on fibrinogen was no longer significant. HRT (n = 21) significantly reversed the menopause-related changes in factor VII (94 ± 15%), even after adjustment for confounding factors. The same trend in both fibrinogen (294 ± 46 mg/dl) and PAI (8.22 ± 5.51 U/ml) was observed. Similar results were found in women using oral or percutaneous estrogen. Our findings suggest that 17-β estradiol in combination with progestins may protect against an increased thrombotic tendency in postmenopausal women. Randomized clinical trials are urgently needed for a better understanding of HRT effect on atherothrombotic process.